The Effectiveness of Implementing Teaching Materials Through E-Learning Media and Youtube to Improve the Learning of Physical Education Sport and Health - Isatul Hasanah; Adi Wijayanto (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
The development of science and technology in this globalization era has had a big impact on whole fields, especially in education. The study aims to learn the effectiveness of teaching materials through e-learning media and youtube to improve the results of study sports and health. This research is a quantitative. The sample was 65 students of elementary students. The data analysis used by researchers is the percentage statistical formula. The finding of this research is that the use of e-learning media with web form is more interest to the students than youtube as a medium for learning sports and health. The Percentages are obtained 77% for use e-learning media and 22% for youtube. The use of  e-learning media can also minimize the boredom experienced by students during the learning process. It can be proved that 57% of students answering with the affirmative answer category and 40% rate by the affirmative answer category. Students are also have enthusiastic when teachers use e-learning rather than youtube media in the learning process with 66% affirmative answer and 17% agree. When the learning is done at home, the students freely use social media. The use of social media cannot be controlled whether in positive or negative ways. Based on the these data obtained by researchers that students are using a 40% level of social media to engage in entertainment such as gaming and 41% to learn physical education materials related to sports and health. Therefore, the use of e-learning media is effective in improving students' learning.